Factors influencing the prevalence of anaemia in female adolescents: A population-based study of rural setting in Karanganyar, Indonesia - Fathimah Sulistyowati Sigit; Fiyan Bahrul Ilmi; Prisilla Desfiandi; Dewantari Saputri; Nur Dwi Fajarini; Ana Susianti; Latifah Agustina Lestari; Asaduddien Faras (Elsevier, 2024)
Background: Anaemia among women of reproductive age (15-49 years) poses substantial public health concerns, particularly in LMICs, due to its adverse effects during pregnancy and childbirth. Understanding its determinants is pivotal for devising strategies to combat this condition. This study investigates the prevalence of anaemia and its associations with anthropometric indices, dietary habits, and menstruation status among female adolescents in Karanganyar, a rural subdistrict in Indonesia. Methods: In this population-based cross-sectional study, a multi-stage sampling method was employed to represent all female high-school students in Karanganyar. Participants underwent capillary haemoglobin testing, anthropometric measurements, and completed dietary intake and menstruation status assessments. Anaemia was defined as Hb < 12.0 g/dL. Logistic regressions were performed to assess the associations between anthropometric indices, dietary intake, menstruation status, and the prevalence of anaemia. Results: Approximately 49 % of female adolescents in Karanganyar had anemia. Both BMI and Mid-Upper-Arm-Circumference exhibited inverse associations with anaemia [AOR(95%CI): 0.87(0.79-0.95) and 0.89(0.81-0.99)]. Compared to individuals with BMI-for-age-Z-Score (BAZ) > -2 SD, those with BAZ < −2 SD had more than double the odds of anaemia [2.43 (0.94-6.29)]. Consumption of fruits [0.32(0.10-0.98)] and vegetables [0.30(0.11-0.78)] were negatively associated with anaemia. No association was observed between menstruation status (length, duration, pads/day) and anaemia. Discussion: High prevalence of anaemia among female adolescents in Karanganyar, and potentially other rural areas in Indonesia, underscores the need for targeted interventions. Being underweight rapidly increases the risk of anaemia, emphasizing the importance of nutritional improvements. Consuming iron-rich fruits and vegetables may prevent anaemia. Menstruation status did not appear to be a determinant of anaemia.